2015
DOI: 10.1371/journal.pone.0123772
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytic Myeloid Derived Suppressor Cells Expansion during Active Pulmonary Tuberculosis Is Associated with High Nitric Oxide Plasma Level

Abstract: Tuberculosis (TB) is still the principal cause of death caused by a single infectious agent, and the balance between the bacillus and host defense mechanisms reflects the different manifestations of the pathology. The aim of this work was to study the role of myeloid-derived suppressor cells (MDSCs) during active pulmonary tuberculosis at the site of infection. We observed an expansion of MDSCs in the lung and blood of patients with active TB, which are correlated with an enhanced amount of nitric oxide in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 21 publications
3
86
0
Order By: Relevance
“…The study found a strong correlation between the accumulation of MDSCs and lethality of disease and suggested that host‐directed therapies targeting depletion of MDSCs could provide a vital breakthrough in ameliorating the disease. These findings were corroborated in humans, where increased expansion of MDSCs in bronchoalveolar lavage, as well as in peripheral blood, of pulmonary TB patients was observed as compared to healthy donors . However, one key question that remains is what controls the expansion of MDSCs in TB‐susceptible and TB‐resistant humans, and how?…”
Section: Macrophage Heterogeneity and M Tuberculosis Infectionmentioning
confidence: 63%
See 2 more Smart Citations
“…The study found a strong correlation between the accumulation of MDSCs and lethality of disease and suggested that host‐directed therapies targeting depletion of MDSCs could provide a vital breakthrough in ameliorating the disease. These findings were corroborated in humans, where increased expansion of MDSCs in bronchoalveolar lavage, as well as in peripheral blood, of pulmonary TB patients was observed as compared to healthy donors . However, one key question that remains is what controls the expansion of MDSCs in TB‐susceptible and TB‐resistant humans, and how?…”
Section: Macrophage Heterogeneity and M Tuberculosis Infectionmentioning
confidence: 63%
“…Infected monocytes/macrophages can reach the bone marrow and interact with hematopoietic stem cells (HSCs) and educate them for generating epigenetically modified macrophages that are much more competent in innate immune response than naive macrophages . Myeloid‐derived suppressor cells (MDSCs) can also be recruited at the site of infection and can negatively influence infection control by inhibiting macrophage and T cell responses via the cytokines and chemokines they produce …”
Section: Macrophage Heterogeneity and M Tuberculosis Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…136 Mesenchymal stromal cells (MSC) are nonhematopoietic progenitor cells with immunomodulatory and antibacterial properties, [137][138] that improve immune responses and lung pathology in human and murine TB. [139][140] Another immunotherapeutic approach involves modulation of immune regulatory cells, specifically myeloid-derived suppressor cells (MDSC) [141][142] MDSC are increased in TB, display T-cell immunosuppressive properties, [143][144][145] and harbour Mtb, suggesting that MDSC-targeting strategies should also be considered in TB HDT design. The promise of use T-cell therapy, with or without T-cell receptor (TCR) manipulations to increase affinity for antigen has shown promise for CMV treatment, and could be beneficial in TB.…”
Section: Cellular Therapymentioning
confidence: 99%
“…This is in part due to the host‐derived immune suppressive cells such as myeloid‐derived suppressor cells (MDSCs). The accumulation of MDSCs hinders protective immune responses to cancer and infectious diseases such as tuberculosis, AIDS, hepatitis C, hepatitis B, pneumonia, and Staphylococcus aurous infection . Importantly, an elevation of MDSCs is associated with a reduced efficacy of vaccines .…”
Section: Introductionmentioning
confidence: 99%